A clinical efficacy analysis of single-port thoracoscopic lung resection in the treatment of male patients with non-small cell lung cancer using surface localization and CT-guided sclerosant - Qinghua Wang; Yujie He; Xiaowei Xie; Qinghua Wu (Journal of Men's Health)
Background: This study was done to explore the effectiveness of single-port thoracoscopic anatomical lung wedge resection in conjunction with Computed Tomography (CT)-guided sclerosants and surface localization for treating male patients diagnosed with non-small cell lung cancer (NSCLC). Methods: A retrospective analysis was conducted on the clinical data of 122 male NSCLC patients treated at our hospital from January 2020 to January 2022. Patients were divided into a study group (61 cases receiving single-port thoracoscopic anatomical wedge resection + CT-guided sclerosant and surface localization) and a control group (61 cases receiving single-port thoracoscopic anatomical wedge resection). The perioperative indicators, serum tumor markers, pulmonary function indicators and stress response indicators were compared between the two groups. Results: Postoperatively, the study group had shorter operation time (124.15 ± 12.52 minutes), hospital stay (7.38 ± 0.73 days), drainage tube removal time (5.75 ± 0.57 days), and lower levels of Cytokeratin 19 fragment (CYFRA21-1) (3.03 ± 0.51 ng/mL), Carcino-Embryonic Antigen (CEA) (9.77 ± 0.96 ng/mL), Cancer Antigen 19-9 (CA199) (45.57 ± 4.86 U/mL), Squamous Cell Carcinoma Antigen (SCC) (21.29 ± 2.38 g/L), Epinephrine (E) (60.87 ± 6.41 pg/mL), Norepinephrine (NE) (185.32 ± 18.53 pg/mL), and Cortisol (Cor) (97.63 ± 9.76 ng/mL) compared to the control group (operation time: 136.85 ± 13.77 minutes; hospital stay: 9.67 ± 0.91 days; drainage tube removal time: 7.23 ± 0.69 days; CYFRA21-1: 4.87 ± 0.55 ng/mL; CEA: 12.68 ± 1.32 ng/mL; CA199: 16.38 ± 1.59 U/mL; SCC: 10.58 ± 1.12 g/L; E: 77.86 ± 7.86 pg/mL; NE: 226.76 ± 22.66 pg/mL; Cor: 119.87 ± 11.89 ng/mL). Conclusions: In summary, the integration of thoracoscopic anatomical lung wedge resection through a single port with CT-guided sclerosant and surface localization has been shown to bring about notable improvements in perioperative parameters, preserve lung function and alleviate stress reactions in male patients diagnosed with NSCLC.